The mechanism of empowering human resources in modern administrative thought - Abdelkader, Garadi; Kouider, Nebeg; Merrad, Mustapha (International journal of economic perspectives, 2024)
The administrative empowerment of modern management, which focuses on the employees and give them the authority and full powers, in order to strengthen the relationship between them and the organization, so as to motivate them to provide their creative and innovative ideas, encourage managers to give their staff powers, and give them confidence and responsibility, And give them authority in the implementation of their tasks, without the direct intervention of the senior management and the break administrative administrative efforts between the internal management and employees. This is why the importance of empowering employees is essential to the success of institutions and adapting them to the changes taking into account that the organization is active within the conditions of an environment characterized by dynamic and rapid change and its unity, considering that it represents an open system that grows and interacts with the opportunities and challenges of the environment in which it is active. This is in order to ensure its continuity and maintain its competitive position. This is what I seek to identify in this research, by addressing the definition of empowerment and the theories that explain it, in addition to the bases on which it is based.